Electro-coalescence of two charged droplets under constant and pulsed DC electric fields. (July 2016) - Wang, Bing-Bing; Wang, Xiao-Dong; Wang, Tian-Hu; Lu, Gui; Yan, Wei-Mon
Highlights: Electrocoalescence of droplets under pulsed DC electric fields is studied. Critical electric field is determined. Higher electro-coalescence efficiency is achieved. Effects of pulse period and duty ratio are presented. Abstract: In the presence of electric field induced by either constant or pulsed direct current (DC), a critical electric strength ( E c ) exists for the transition from full coalescence to partial coalescence of adjacent charged droplets. In this study, the electro-coalescence behaviors of two charged droplets under constant and pulsed DC electric fields are studied via molecular dynamics simulations. The results show that the two droplets experience an attractive force when the constant DC electric field is applied, which causes an accelerated approach from one another before contact. However, under the pulsed DC electric field, the approach velocities of the two droplets accelerate within the pulse duration, while remain approximately constant during the pulse interval. Thus, the value of E c for full coalescence and partial coalescence of the two droplets under the pulsed DC electric field becomes larger as compared with the constant DC electric field, which significantly reduces the time required for bringing the two droplets into contact. Hence, higher electro-coalescence efficiency is achieved. Furthermore, for a given pulse period, E c is inversely proportional to the pulse duration; for a given duty ratio, E c reduces with the increase in the pulse period.